Annexin-2, pentraxin-3, and osteopontin expressions in the endometrium of women with idiopathic recurrent pregnancy loss during the implantation window - Şahin, Banuhan; Alataş, Erkan; Özkan, Sevgi (Journal of Surgery and Medicine, 2020)
Aim: Failed expression of endometrial receptivity molecules and genes during the implantation window may lead to idiopathic recurrent pregnancy loss (IRPL). The aim of this study was to investigate annexin-2 (ANXA-2), pentraxin-3 (PTX-3) and osteopontin (OPN) expressions in the endometrium of women with IRPL.Methods: A total of 34 women with IRPL and 34 age-matched healthy women were recruited in this case control study. Serum samples were collected in the mid-luteal phase of the menstrual cycle and endometrial biopsies were harvested in the window of implantation days. The expressions of ANXA-2, PTX-3, and OPN in the endometrial biopsies according to localizations were examined by immunohistochemistry. The H-score method was used to evaluate the intensity of endometrial ANXA-2, PTX-3, and OPN immune-reactivity.Results: The mean PTX-3 score was significantly higher in the epithelial endometrium of women with IRPL compared with control cases (2.47 (0.56) vs 1.44 (0.50), P<0.001). Both luminal and glandular epithelial and stromal components of the endometrium showed increased staining for PTX-3 in women with IRPL. The increase of PTX-3 expression in the epithelial endometrium correlated with the decrease of serum progesterone level (P=0.016). When ANXA-2 and OPN expressions in the epithelial endometrium of IRPL samples were compared with the age-matched control subjects, although there was lower expression, no statistically significant difference was observed (1.97 (0.71) vs 2.21 (0.59), P=0.145 and 1.97 (0.79) vs 2.12 (0.68), P=0.418).Conclusion: PTX-3 expression increases in the epithelial and stromal endometrium of women with IRPL during the implantation window. As the serum progesterone level decreases, endometrial PTX-3 expression increases in glandular and luminal epithelium in women with IRPL. Endometrial PTX-3 may be a potential molecular target for IRPL.